Peran Burnout sebagai Mediasi pada Pengaruh Stres Kerja Terhadap Kinerja Karyawan - Ryani Dhyan Parashakti; Muhamad Ekhsan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Employees are an important asset for the company, because the productivity of the company is on them. Therefore the company must have its employees very well so that employees feel comfortable. The comfort factor for employees is something that must be considered by the company so that employees feel at home working at the company so that employees become loyal, so that their performance becomes better. In fact, if employees feel uncomfortable, it will cause work stress that can cause stress. This study aims to see the effect of stress on performance mediated by burnout. Respondents consisted of 81 employees of PD 2.2 Common Rail. Methods and data using a questionnaire. Data processing techniques using Smart PLS, the results of this study indicate that: first, job stress does not have a positive and significant effect on employee performance variables. Second, performance has a positive and significant effect on Burnout. Third, Job Stress has a positive and significant effect on the Burnout variable. fourth, work stress and performance have a positive and significant effect on Burnout.